2018 Flow Control Conference 2018
DOI: 10.2514/6.2018-4016
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Unsteady Excitation of Separated Flow over the NASA Hump Model

Abstract: Separated flow and its control over the NASA hump model were investigated at subsonic speeds. Three-dimensional, unsteady fluid dynamic simulations were supplemented by wind tunnel measurements. Flow control was implemented by means of spatially distributed discrete jets operating in steady and unsteady modes. The effects of excitation amplitude and frequency were studied numerically and experimentally. Several integral parameters were explored as quality metrics. In addition to the existing ones, two new inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Unlike the unsteady synchronized actuations in Refs. [15,21], the random oscillations of the fluidic oscillator jet do not cause vortex shedding associated with the flow separation bubble. Fluctuating pressures in the pressure recovery region with varying momentum coefficient are presented in Figure 10b.…”
Section: Unsteady Pressure Measurementsmentioning
confidence: 94%
See 2 more Smart Citations
“…Unlike the unsteady synchronized actuations in Refs. [15,21], the random oscillations of the fluidic oscillator jet do not cause vortex shedding associated with the flow separation bubble. Fluctuating pressures in the pressure recovery region with varying momentum coefficient are presented in Figure 10b.…”
Section: Unsteady Pressure Measurementsmentioning
confidence: 94%
“…The pressure appears to be recovered downstream of the model trailing edge near x/c = 1.3 due to the separated flow and the splitter plate. The inviscid flow solution of the three-dimensional hump model [21] is also presented in this figure. The ideal (i.e., inviscid) flow over the hump model results in more flow deceleration near the leading edge of the model and more acceleration afterward.…”
Section: Baseline Separated Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that fluidic oscillators are almost always superior to steady jets with respect to any flow control coefficient at a given spacing. Koklu (2018), studied the effects of excitation amplitude and frequency, both numerically and experimentally, on separated flow and its control over the NASA hump model at subsonic speeds by using discrete jets operating in steady and unsteady modes. It was revealed that the unsteady excitation is superior to the steady excitation and a bit better than the sweeping jet actuators while the steady suction was found to be the most effective.…”
Section: Introductionmentioning
confidence: 99%